Commodity research on natural leather as a component of quality management of footwear materials (Economics and region, 2025)
The article examines the problems of modern fashion industry production, in particular the production of materials for footwear and footwear in general, in the context of sustainable development. It is proven that the fashion industry is one of the largest sources of environmental pollution, and the maximum percentage of waste is formed from shoe waste (materials for its production) after consumption, that is, after the end of the service life of the shoe, which mainly ends up in landfills. It is proven that the production and operation of environmentally friendly shoes is one of the priority areas of sustainable development of the fashion industry, and the production of environmentally friendly shoes involves reducing the carbon footprint, using organic, recycled materials, etc.The feasibility of establishing environmentally conscious production, including materials for the production of leather footwear, is substantiated. The basic principles for the production of environmentally friendly footwear are formulated and presented. The leading world results of commodity research, innovations and developments aimed at reducing and/or eliminating the negative impact on the environment from production in the fashion industry, in particular the leather and footwear industry, are presented. Examples of proposed ways to solve the problem of sustainable production of footwear materials are given and the feasibility of using a new concept of processing chromium waste from the production of genuine leather, taking into account the principles of the circular economy, is proven. The use of one of the foreign methods of ecological orientation in the production of natural leather in the domestic industry is proposed, namely, the use of recovered chromium from leather production waste as tanning substances for the subsequent production of natural leather. The results of research on natural leather for footwear purposes, including that made using recovered chromium during tanning, are presented and analyzed. The possibility of using such natural leather in domestic shoe production is proven.
Keywords: footwear; natural leather; assortment; quality management; innovation; consumer properties; circular economy